The effects of pulse exposures of metal toxicants on different life stages of the tropical copepod Acartia sinjiensis. (15th September 2021) - Stone, Sarah; McKnight, Kitty; Legendre, Laura; Koppel, Darren J.; Binet, Monique T.; Simpson, Stuart L.; Jolley, Dianne F.
Abstract: Effluent discharges can potentially result in high concentrations of metals entering aquatic environments for short durations, ranging from a few hours to days. The environmental risks of such exposures are challenging to accurately assess. Risk assessment tools for effluent discharges include comparison of toxicant concentrations with guideline values and the use of direct toxicity assessments, both of which were designed to assess continuous, rather than pulse, contaminant exposures. In this study, a chronic pulse-exposure toxicity test was developed using the tropical euryhaline calanoid copepod Acartia sinjiensis . This copepod has a rapid life cycle and is highly sensitive to metal contaminants, with 50% effect concentrations (chronic EC50) for larval development of 1.7, 8.6 and 0.7 μg L −1 for copper, nickel and zinc, respectively. The toxicities of copper and nickel were assessed as a continuous exposure (78 h) and as pulses (3, 6 and 18 h) initiated at varying life stages, from egg to copepodite, and measured larval development over 78 h. Generally, 24-h old nauplii were more sensitive or of similar sensitivity to copper and nickel pulses than 48-h old nauplii. The 78-h test duration enabled observations of chronic effects following pulse exposures, which frequently occurred in the absence of acute effects. The EC50 values for pulse exposures were higher than those of continuous exposure by up to approximately 16-fold and 15-fold for copper and nickel, respectively. When metal-pulse exposure concentrations were expressed using the time-weighted averaged concentration (TAC), resultant concentration response curves were similar to those in continuous exposures to the same metal, suggesting that thresholds based on continuous exposures were also protective for pulse exposures to these metals. This research improves our understanding of the toxicity of pulse contaminant exposures and assists with developing improved approaches to for the risk assessment and regulation of short-term contaminant discharges. Graphical abstract: Image 1 Highlights: Early life stage nauplii more sensitive than eggs, late nauplii and copepodites. Pulse toxicity estimates similar when compared using time averaged concentrations. Pulse exposures not affecting population sometimes caused development effects. Chronic toxicity of Cu and Ni increased with increasing duration of pulse exposure. Continuous exposure thresholds were highly protective of pulse exposures. Abstract : The toxicity of metals from continuous and short-term exposures was assessed for marine copepod populations. Threshold concentrations for continuous exposures were protective of pulse exposures with organism life-stage and exposure duration affecting both larval development and population size.